Neuroeducation sebagai Paradigma Baru dalam Pedagogi Kontemporer: Integrasi Neurosains untuk Transformasi Pendidikan Abad 21 - Mizlan; Zalila, Nur (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The transformation of education in the 21st century requires more adaptive, scientific, and integrated pedagogical approaches. One emerging paradigm is neuroeducation, an interdisciplinary integration of neuroscience, cognitive psychology, and pedagogy aimed at enhancing the quality of teaching and learning. This study systematically examines the role of neuroeducation in contemporary education by identifying implementation strategies, challenges, and its implications for educational policy. The method used was a systematic literature review (SLR) involving 20 peer-reviewed articles published between 2015 and 2025, retrieved from Scopus, ScienceDirect, and SINTA databases. The findings reveal that neuroeducation significantly contributes to improving learning outcomes through multisensory teaching, reinforcement of neuroplasticity, and restorative pedagogical approaches. Nevertheless, several challenges persist, particularly related to the limited neuroscience literacy among teachers and the lack of structured training programs. This study recommends the systematic integration of neuroeducation concepts into teacher education curricula and national education policy.